Analysis on the Selection Rules of Acupoints for Acupuncture Treatment of Breast Hyperplasia - Shang, Ruitong; Ren, Yuanyuan; Xia, Ying; Liu, Peng (Journal of Contemporary Medical Practice, 2024)
Objective: To summarize the acupoints selected by acupuncture in the treatment of breast hyperplasia by reading the literature, and to clarify the rules of acupuncture in the treatment of breast hyperplasia. Methods: The literature was searched and screened with the keywords "acupuncture" and "breast hyperplasia" in CNKI, and 32 acupuncture methods for the treatment of breast hyperplasia were selected and summarized. Results: The most frequently used acupoints were Danzhong, Sanyinjiao, Taichong, Zusanli, Ganshu, Wuyi and Rugen. The meridians that are more used are the Zuyang Ming Stomach Meridian, the Zuyang Bladder Meridian, the Zu Yin Liver Meridian, and the Ren Meridian; The treatment uses more chest acupoints. Conclusion: Acupuncture has a clear curative effect in the treatment of breast hyperplasia, and the acupoint selection rule is mainly based on the acupuncture points of the stomach meridian of Zuyangming, supplemented by the acupoint of the foot sun bladder meridian and the yin and liver meridians of the foot and the yin and liver meridians of the foot and the pulse. The application of local acupoint selection treatment, supplemented by the acupoints of the lower limbs.